Improving Function in Cavernous Sinus Meningiomas: A Modern Treatment Algorithm - Beer-Furlan, André; Priddy, Blake H.; Jamshidi, Ali O.; Shaikhouni, Ammar; Prevedello, Luciano M.; Ditzel Filho, Leo; Otto, Bradley A.; Carrau, Ricardo L.; Prevedello, Daniel M. (Frontiers in Neurology, 2020)
Background: The efficacy and safety of radiosurgery led to paradigm shift in the management of cavernous sinus meningiomas. Nevertheless, patients are still significantly affected by cranial nerve deficits related to the mass effect of these tumors. Our management strategy involves the combination of a functional surgical decompression followed by radiation therapy. Methods: We reviewed a single institution’s cohort of patients that underwent EED for symptomatic meningiomas primarily involving the CS from 2010 to 2016. The preoperative neuro-ophthalmological exam was compared to the 1-month and 6-month postoperative exams.The patient’s length of hospital stay, complications, radiological and clinical follow up were noted. Results: A total of 17 patients underwent EED for CS meningiomas that fit our radiological criteria.The final outcome at the 6-month visit showed 5 patients (62.5%) with normalization of deficit and 3 patients (37.5%) with partial improvement of the CNII deficit. Out of the 12 patients that had CSCN deficits, the final outcome at the 6-month visit showed 4 patients (33.33%) with normalization of deficit, 7 patients (58.3%) with partial improvement and 1 patient (8.33%) with no improvement. There were no intraoperative complications. Conclusion: The EED for CS meningiomas is a valuable technique when addressing acute/subacute CNII and CSCN deficits. This conservative surgical approach showed good functional outcomes, low morbidity and low complication rates. However, it does not exempt the need for radiosurgery/radiation therapy for control of tumor growth.